A Case Series on Critically Ill Pregnant or Newly Delivered Patients with Covid-19, Treated at Karolinska University Hospital, Stockholm - Rasha El-ahmad Polcer; Elin Jones; Karin Pettersson (Case Reports in Obstetrics and Gynecology)
In this retrospective report, we present five cases of critically ill pregnant or newly delivered women positive for Covid-19 admitted to our obstetrical departments at Karolinska University Hospital. They compose 6% of eighty-three pregnant women that tested positive for SARS-CoV-2 during the period March 25 to May 4, 2020. Three patients were at the time of admission in gestational week between 21+4 and 22+5 and treated during their antenatal period; meanwhile, the other two were admitted within 1 week postpartum. All of them were in need of intensive care: one was treated with high flow oxygen therapy, the other four with invasive mechanical ventilation (three with endotracheal intubation and one with extracorporeal membrane oxygenation). Age above thirty, overweight, and gestational diabetes are notable factors in the cases presented. At the time of admission, they all presented with symptoms such as fever, cough, and dyspnea. Chest imaging with computer tomography scan was performed in each case and demonstrated multifocal pneumonic infiltrates in all of them, but no pulmonary embolism was confirmed in any. Neither did the echocardiogram indicate any cardiomyopathy. Four of the patients have been discharged from the hospital, with an average of 20 hospital days. One antenatal pregnant woman needed prolonged ECMO therapy; in gestational week 27+3, she went into cardiac arrest, resulting in an urgent C-section on maternal indication. At the time of writing, she is still hospitalized. In coherence with other published reports, our cases indicate that critically ill pregnant women infected by SARS-Cov-2 may develop severe respiratory distress syndrome requiring prolonged intensive care. The material is limited for conclusions to be made; more detailed information on symptoms, treatment, and outcomes for pregnant and postpartum women managed in intensive care is therefore needed.